Effectiveness and applications of neurologic music therapy in motor and non-motor rehabilitation for older adults with Parkinson’s disease: a systematic review and meta-analysis - Li, Aoyi; Yang, Yiyao; Jiang, Qiyu; Wu, Tiantian; Li, Tiantian (Frontiers in Neurology, 2025)
PurposeTo systematically assess the current status and effectiveness of neurologic music therapy in the rehabilitation of older adults with Parkinson’s disease.Materials and methodsA comprehensive search was conducted for randomized controlled trials. Studies were selected according to predefined inclusion and exclusion criteria. The review followed PRISMA guidelines, and methodological quality was appraised using the RoB 2.ResultsTen RCTs involving 529 older adults with PD, published mainly between 2011 and 2022, were included. Meta-analysis showed neurologic music therapy significantly improved gait velocity (SMD = 0.70, 95% CI [0.39, 1.01], p < 0.001) and stride length (SMD = 0.63, 95% CI [0.39, 0.88], p < 0.001), with moderate effect sizes, but no significant effect on cadence (SMD = 0.14, 95% CI [−0.46, 0.74], p = 0.65). Balance showed small-to-moderate improvement (SMD = 0.35, 95% CI [0.04, 0.66], p = 0.028), which became nonsignificant after sensitivity analysis (SMD = 0.29, 95% CI [−0.04, 0.62], p = 0.085).ConclusionThe available evidence suggests that NMT, especially RAS, shows moderate effects in improving gait speed and stride length, with relatively consistent support across studies. However, findings on cadence remain limited and are characterized by high heterogeneity. With respect to balance, pooled analyses indicated a possible mild benefit, but this effect was highly sensitive to specific studies and failed to remain statistically significant. Overall, therefore, the evidence for balance outcomes appears weak and somewhat inconsistent. With respect to quality of life and emotional well-being, the currently available quantitative evidence is both scarce and somewhat inconsistent. It can only suggest a potential benefit in a preliminary sense, and the conclusion is far from solid. More rigorously designed and higher-quality RCTs are urgently needed to confirm these findings.